Wearable Kinesthetic System In Post-Stroke Rehabilitation: A Review Of Sensor In Body Motions Detection - Mohd Ali, Nursabillilah; Chan, Albert Bao Der; Ko, Christina Yun Fan; Law, Kok Wah; Loh, Mun Loong; Sulaiman, Marizan; Hasan, Zulhasnizam; Hussin, Mohamed Saiful Firdaus; Razali, Sazalinsyah (Penerbit Universiti Teknikal Malaysia Melaka, 2018)
This paper presents a system with various kinematics parameters considered to capture and classify body gestures for user’s recovery. The concepts involved are briefly explained in this paper. Basically, two devices concepts are explained, which are the Upper Limb Kinesthetic Garment (ULKG) and OPAL technologies. The method of literature search used is discussed in methodology, while detailed information from reviews on particular devices is analysed. Then, the performance and feedback from users are compiled to indicate usability on both devices under the results section. Both ULKG that used conductive elastomer (CE) and OPAL sensor are compared to figure out which sensor is more appropriate for users.